Anisakis simplex Rudolphi 1809, s.l. ... - Hernández-Orts, Jesús S.; Viola, M. Natalia Paso; García, Néstor A.; Crespo, Enrique A.; González, Raúl; García-Varela, Martín; Kuchta, Roman (Zenodo, 2015)
Anisakis simplex (Rudolphi, 1809) s.l. Host: Cephalorhynchus commersonii (Lacépède) Site in host: intestine, stomach Developmental stage: L3 Locality: Tierra del Fuego province; central Patagonia and San Jorge Gulf (45º–47ºS) References: Berón-Vera et al. (2001) Host: Delphinus delphis Linnaeus Site in host: forestomach, pyloric stomach Developmental stage: L3, L4 Locality: Claromecó (38º52'S, 60º05'W) and Necochea (38º27'S, 58º50'W), Buenos Aires province; northern Patagonia (39º–42ºS, 60º–62ºW) 4. Third-stage larvae (L3) of anisakid nematodes are recently acquired larval forms, which infect marine mammals when they prey on cephalopods and fish (McClelland 2002; Klimpel et al. 2004). In marine mammals, the L3 moult into the fourth-stage larva (L4) and then into adult. Specimens in collections: BMNH (1993.5201–5205)V; MZU (accession numbers not provided)V; USNPC (99622)V References: Aznar et al. (2003) and Berón-Vera et al. (2007) Host: Lagenorhynchus cruciger (Quoy & Gaimard) Site in host: stomach ... : Published as part of Hernández-Orts, Jesús S., Viola, M. Natalia Paso, García, Néstor A., Crespo, Enrique A., González, Raúl, García-Varela, Martín & Kuchta, Roman, 2015, A checklist of the helminth parasites of marine mammals from Argentina, pp. 301-334 in Zootaxa 3936 (3) on pages 313-314, DOI: 10.11646/zootaxa.3936.3.1, http://zenodo.org/record/236696 ...